A Derivation of a Variable Vertical Mesh Spacing for Les Models: Application To a CBL - Degrazia, G. A.; Rizza, U.; Puhales, F. S.; Goulart, A. G. O.; Carvalho, J. C. (Ciência e Natura, 2007)
A derivation of a variable vertical mesh spacing for LESmodels: application to a CBL